Ultrastructural Alterations in Lepocinclis acus (Euglenophyta) Induced by Medium with High Organic Matter Content - Conforti, Visitación T.; Ruiz, Laura B.; Leonardi, Patricia I. (Frontiers in Ecology and Evolution, 2017)
Ultrastructural changes induced by exposure to excess of organic matter were studied in Lepocinclis acus (ex Euglena acus). The cells isolated from the Matanza River, Buenos Aires, Argentina, were grown in soil water medium. When transferred to medium enriched with Bacteriological Peptone OXOID®, marked body deformation and a significant shortening and widening of the cells was observed. These changes were unexpected in a species with quite rigid cells, a condition previously shown in studies of the pellicle fine structure. Transmission electron microscopy observations suggest that cellular deformation might be facilitated by an increase in strip number, whereas in the original strips normal ultrastructure was maintained. An increase in number and volume of paramylon grains and vacuoles, as well as the presence of membrane whorls in vacuoles was observed. The fine structure of organisms grown in medium with and without organic matter enrichment was compared, and the systematic and ecological importance of morphological changes triggered by cell deformation was discussed.